3‐D X‐ray Nanotomography Reveals Different Carbon Deposition Mechanisms in a Single Catalyst Particle. Issue 10 (31st March 2021) - Veselý, Martin; Valadian, Roozbeh; Lohse, Leon Merten; Toepperwien, Mareike; Spiers, Kathryn; Garrevoet, Jan; Vogt, Eelco T. C.; Salditt, Tim; Weckhuysen, Bert M.; Meirer, Florian
Abstract: Catalyst deactivation involves a complex interplay of processes taking place at different length and time scales. Understanding this phenomenon is one of the grand challenges in solid catalyst characterization. A process contributing to deactivation is carbon deposition (i. e., coking), which reduces catalyst activity by limiting diffusion and blocking active sites. However, characterizing coke formation and its effects remains challenging as it involves both the organic and inorganic phase of the catalytic process and length scales from the atomic scale to the scale of the catalyst body. Here we present a combination of hard X‐ray imaging techniques able to visualize in 3‐D the distribution, effect and nature of carbon deposits in the macro‐pore space of an entire industrially used catalyst particle. Our findings provide direct evidence for coke promoting effects of metal poisons, pore clogging by coke, and a correlation between carbon nature and its location. These results provide a better understanding of the coking process, its relation to catalyst deactivation and new insights into the efficiency of the industrial scale process of fluid catalytic cracking. Abstract : Tomography bears : Carbon deposits within a whole catalyst particle are visualized by 3‐D X‐ray Holotomography by imaging in a differential mode. The 3‐D distribution allows quantification of pore clogging by coke and a correlation between carbon nature and its location. Moreover, correlative 3‐D X‐ray Fluorescence tomography bears out coke promoting effects of metal poisons.